BEYOND METRICS: Performance Management Dynamics in Indonesian Public Sector Energy and Mineral Resources Governance - Munawaroh, Munawaroh; Ginanjar, Egi; Wibowo, Raditya; Cahyawati, Atiq; Putri, Adela Winda Iryana (Yayasan Education and Social Center, 2026)
Performance management systems in public sector organizations confront distinctive challenges balancing accountability imperatives with operational complexities, particularly within technically demanding domains like energy and mineral resources governance. This qualitative case study examines performance management system dynamics at Banten Province Energy and Mineral Resources Agency, investigating planning, monitoring, and evaluation processes alongside civil servant interpretations of system implementation. Through semi-structured interviews with purposively-selected officials and operational staff, direct administrative process observations, and systematic document analysis encompassing strategic plans, performance indicators, and institutional reports, research reveals four critical findings: hierarchical performance planning demonstrates regulatory adaptability despite resource constraints; monitoring combines formal mechanisms with digital systems though communication challenges persist; evaluation processes maintain systematic procedures yet retain subjectivity potential in behavioral assessments; and system implementation fosters disciplined, professional, accountable organizational culture despite administrative burden concerns and limited digital integration. Findings enrich understanding of public sector performance management's dynamic character while providing theoretical and practical implications for strengthening performance systems in strategic Indonesian government sectors. Research contributes empirically-grounded insights from underexplored energy-mineral governance contexts, offering evidence-based recommendations for reconciling performance measurement rigor with sectoral operational realities.